EDITOR'S PREFACE - Achmad Zainal Arifin (Jurnal Sosiologi Reflektif, 2022)
Alhamdulillah, thank you be to Allah for the publication of Jurnal Sosiologi Reflektif (JSR) Vol.16 No.2 in 2022. After a little delay due to the moment of Ramadan and Eid Al-Fitr, JSR is able to greet all readers again. The outline of the article from this edition is the result of the 6th JSR Panel Conference held on November 24-25, 2021. The theme of the 6th panel conference is: "Social Changes After Pandemic: Reinterpreting Everyday Life of Muslim Society". Therefore, seven articles in this edition discuss various aspects of life related to how Muslim societies across the country responding to the phenomena of Covid-19 pandemic, which nearly come to the end. Meanwhile, the rest of articles in this edition are added to acknowledge other actual issues outside the boundaries of pandemic.The main articles related to the issues of Covid-19 pandemic begins with the article of Maftukha. She describes religious holydays in Indonesia, especially among Muslims and Christians in North Sulawesi contribute to strengthen the solidarity of people, which is weakened during the pandemic due to some restrictions policies in conducting daily religious activities. Similar issue is also raised by Andi Azis Putra who gives more attention on how to create social cohesion during the pandemic situation using the case of digital voluntarism in elevating religious consciousness among Indonesian netizen. Another interesting aspect in responding the Covid-19 is related to the issue of the higher usage of digital media platform in religious practices as proposed by Abd. Hannan with the issue of various disruptions in practicing religious worship, Romario with the issue of new media in portraying religious authority in the case of conspiracy discourse, Yulianti and Khoniq Nur Afifah with an issue on challenging the Islamic philanthropy in empowering Muslim society during the pandemic; Hajar Gelis Pramudyasmono with his conclusion of his research that there is no significant influence on the implementation of health’s protocols to the social and economic activities of society in Bengkulu Province, and also Ahmad Norma Permata et.al., with some interesting changes in leisure, safety, and continuity of post-pandemic tourism.Other issues outside the Covid-19 pandemic raised in this edition are related to dakwah strategy among the youth Muslims and the issues of gender. Changing the dakwah model among youth Muslims, especially in urban areas, is quite fascinating. Eko Saputra portrays how Teras Dakwah in Yogyakarta, for example, using cafes as a complementary place for mosques or other conventional religious sites to learn Islam. Learning Islam in cafes becomes more interesting phenomenon for youth Muslims in some urban areas. Gender issues are still attractive to be discussed during the pandemic era, including a traditional controversial issue on the practice of polygamy. Nur Afni Khafsoh, et.al., for instance, criticizing the practice of polygamy in Indonesia by observing the thoughts of three prominent figures of Muslim scholars in order to minimize misunderstanding on how the practice of polygamy perceived by Indonesian Muslims. Another issue related to gender and family is raised by Trias Novita Elisadayna with a paper title on “Sociological Analysis of Sexual Satisfaction in Individual with Marriage Age under Ten Years”. She concluded that physical health, strong financial support, numbers of child, and healthy relationship in child care have a positive function in creating happiness and stability in the family, including through sexual satisfaction of both partners. Last but not least, Muhammad Alhada Fuadul Habib, et.al., raised an important issue on the impacts of post-conflict in building a New Yogyakarta International Airport (NYIA) for surrounding areas, especially related to social and economic development of the people.Finally, we hope all articles presented in this edition will enrich our knowledge and lift up our understanding on several important issues on improving the quality life of society. We are fully aware that this edition is still far from perfection, therefore we are open for any critics to preserve the quality of our journal. Thank you and enjoy reading this edition.Regards,Editor in-Chief of JSR  Achmad Zainal Arifin, Ph.D